1975
DOI: 10.2307/2345215
|View full text |Cite
|
Sign up to set email alerts
|

Whose Cost of Living?

Abstract: The usual form of retail price index implicitly gives each household a weight proportional to its total expenditure. An index of this form is appropriate, e.g, for deflating the total wage-bill. But the retail price index is more frequently used as a measure of price changes applying on average to a group of families or a class of wage-earners. For such purposes, it is appropriate to estimate the average change by using"democratic" weights, i.e. the same weight for every household, or weights proportional to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…Of course, the non-homotheticity of preferences also implies that the CPI, which is a single price index, estimates the cost of living at one point in the income distribution an observation made long ago by Prais (1959) and Nicholson (1975). Therefore the implication of preferences being non-homothetic is that the CPI and P t each estimate a cost of living index for a specic level of income, but these two income levels need not be the same.…”
Section: Lost In Translationmentioning
confidence: 99%
“…Of course, the non-homotheticity of preferences also implies that the CPI, which is a single price index, estimates the cost of living at one point in the income distribution an observation made long ago by Prais (1959) and Nicholson (1975). Therefore the implication of preferences being non-homothetic is that the CPI and P t each estimate a cost of living index for a specic level of income, but these two income levels need not be the same.…”
Section: Lost In Translationmentioning
confidence: 99%
“…Because the CPI fails to capture the benefits to consumers from greater availability of products and brands, changes in the cost of living are typically overstated. (Nicholson 1975, Deaton 1998. In times of changing relative prices, such as during food price shocks, inflation measured by the CPI can then differ from the inflation experienced by poorer population groups (Günther and Grimm 2007).…”
Section: Cpi Bias In Sub-saharan Africamentioning
confidence: 99%
“…This research was suggested by Nicholson (1975) but not until Michael (1979), whose work was extended by Hagemann (1982), do we get some estimates of price inflation's varying impact across household types. Slottje (1987) looked at the consequence of relative price changes across income components.…”
Section: Introductionmentioning
confidence: 99%